2022
DOI: 10.3389/fphar.2022.883251
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Coenzyme Q10 Supplementation for Reducing Fatigue: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Coenzyme Q10 (CoQ10) is a popular nutritional supplement, an antioxidant and an essential component of the mitochondrial electron transport chain. Several clinical studies have suggested that fatigue can be reduced by antioxidant supplementation. However, the data on this topic has been sparse to date. Hence, we conducted this meta-analysis with the aim of investigating the effectiveness of fatigue reduction via CoQ10 supplementation. More specifically, we searched electronic databases for randomized controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 67 publications
0
5
0
1
Order By: Relevance
“…In addition, studies demonstrated that CoQ10 deficiency was positively associated with fatigue, whereas serum CoQ10 levels were inversely correlated with fatigue severity ( 46 , 47 ). In addition, another meta-regression also confirmed that a daily dose of CoQ10 was associated with fatigue reduction ( 48 ). Therefore, we suppose that ubiquinol supplementation at high altitudes may alleviate AMS and HADAS-related symptoms and maintain cardiorespiratory fitness.…”
Section: Discussionmentioning
confidence: 82%
“…In addition, studies demonstrated that CoQ10 deficiency was positively associated with fatigue, whereas serum CoQ10 levels were inversely correlated with fatigue severity ( 46 , 47 ). In addition, another meta-regression also confirmed that a daily dose of CoQ10 was associated with fatigue reduction ( 48 ). Therefore, we suppose that ubiquinol supplementation at high altitudes may alleviate AMS and HADAS-related symptoms and maintain cardiorespiratory fitness.…”
Section: Discussionmentioning
confidence: 82%
“…Although the study was adequately powered, no significant differences were detected between the CoQ10 and placebo arms at 24 weeks for scores on the Profile of Mood States Fatigue Subscale ( P = .257) or the FACIT-F tool ( P = .965). Fatigue examined at 24 weeks is adequate to see a clinical response from CoQ10 and the 300 mg total dose is on the upper end used to treat other health conditions, 156 although some studies have used as high as 600 mg/day. All would imply that CoQ10 is not an effective treatment for cancer fatigue.…”
Section: Recommendationsmentioning
confidence: 99%
“…Research has indicated that CoQ10 has demonstrated efficacy in mitigating fatigue, particularly among those afflicted with chronic fatigue syndrome (CFS) (46). CFS is a burdensome medical illness distinguished by the presence of continuous exhaustion that does not ameliorate with periods of rest.…”
Section: Coq10 Enhance Stamina Reduce Fatigue and Improve Overall Exe...mentioning
confidence: 99%